Current polio status in the world - Elaine S. Lima; Eliete C. Romero; Celso Francisco H. Granato (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Poliomyelitis is still an endemic disease in Afghanistan, Nigeria, and Pakistan despite the efforts to eradicate the disease. Therefore, there is a potential risk of international spread. Since the start of the polio eradication program by the Global Polio Eradication Initiative in 1988, the incidence of polio has been reduced by 99%. In the last decade, wild poliovirus type 2 (WPV2) was eliminated and declared eradicated in 2015. Wild poliovirus type 3 (WPV3) was last reported in November 2012. These changes have allowed the removal of Sabin poliovirus type 2 from the oral poliovirus vaccine (OPV) in April 2016 and countries either introduced bivalent OPV (bOPV) containing Sabin types 1 + 3 poliovirus or added at least one dose of inactivated poliovirus vaccine (IPV) into their routine immunization schedule. Many efforts are needed to eradicate polio, and new strategies should be implemented such as the development and approval of new genetically stable OPV, and vaccines that do not require infectious processes for virus growth, such as virus-like particles (VLPs), or packing-cell technology. IPV will increasingly be produced from Sabin strains, and further attenuated or genetically modified strains. Furthermore, there is also a need for the development of antiviral drugs to treat immunodeficient patients who are long-term excretors infected with poliovirus, thus avoiding contamination of individuals susceptible to polioviruses, due to reversal of pathogenicity. If all these measures are successfully implemented, the world will be close to the global